Laparoscopic management of Mirizzi syndrome with liver cirrhosis using indocyanine green mapping: A case report and review of the literature - Priya Gupta; Vishakha Kalikar; Roy Patankar; Advait Patankar (Society of Gastrointestinal Intervention, 2023)
Mirizzi syndrome was previously considered an absolute contraindication for laparoscopic cholecystectomy. However, with advances in radiology and increasing familiarity with the pathophysiology, the successful laparoscopic management of Mirizzi syndrome is now increasingly reported. The presence of cirrhosis and periportal collaterals increases the difficulty of performing laparoscopic cholecystectomy. Intraoperative indocyanine green(ICG) imaging is very helpful in these complex situations. We present the first published report of ICG-assisted laparoscopic cholecystectomy in type 1 Mirizzi syndrome with Child-Pugh A cirrhosis.